EXAFS investigation of Ni(Ⅱ) sorption at the palygorskite-solution interface: New insights into surface-induced precipitation phenomena. (1st December 2021) - Mo, Xinxin; Siebecker, Matthew G.; Gou, Wenxian; Li, Wei
Abstract: Sorption reactions at the mineral/water interface control the fate and transport of trace metals in aqueous geochemical environments. While surface complexation theory is well established, understanding of surface induced precipitation at mineral/water interfaces is still limited. In this research, we employed a combination of macroscopic batch sorption studies, transmission electron microscopy (TEM), diffuse reflectance spectroscopy (DRS), and extended X-ray absorption fine structure (EXAFS) spectroscopy to elucidate the sorption mechanisms of nickel (Ni) at palygorskite/solution interfaces. Compared to extensive studies focused on oxides and layer-structured clay minerals, research on chain-type clay minerals (e.g., palygorskite and sepiolite) is sparse. Thus, novel investigations using chain-type clay minerals can provide new insights into the metal sequestration mechanisms and improve equilibrium modeling. In this work, temperature-dependent kinetic experiments demonstrated that the activation reaction energy ( E a ) for Ni sorption on palygorskite at pH 6.0 is 35.1 kJ mol −1, significantly lower than that of pH 7.5 ( E a  = 102.1 kJ mol −1 ). These values indicated an adsorption reaction at low pH and a precipitation reaction at high pH. EXAFS analysis confirmed that below pH 6, Ni sorption was dominated by outer-sphere surface complexes at low ionic strength (I = 0.01 M) and inner-sphere surface complexation at high ionic strength (I = 0.1 M). Above pH 7.5, EXAFS data suggested the formation of Ni phyllosilicate precipitates, in agreement with its linear sorption isotherm. An important finding is that the precipitates can form at very low Ni concentrations (∼0.07 mM), with the sorption density of Γ = 0.09 μmol m −2, which corresponds to a 0.3% monolayer coverage for palygorskite. In contrast, at this low level of Ni concentration, surface precipitates did not form on γ-Al2 O3 . We propose that Ni can be directly induced to precipitate on the palygorskite surface in a process we term "continuous nucleation". This is mechanistically different from the traditional adsorption-to-polymerization process on the γ-Al2 O3 surface, which we term "staged nucleation". Further testing revealed that a linear-shaped isotherm was also observed for Ni sorption on sepiolite, a clay mineral with similar structure and chemical composition to palygorskite, indicating a similar reactivity for both chain-structure phyllosilicates. This is distinct from the Langmuir-type sorption isotherm observed for Ni reaction with Al oxides and montmorillonite. The findings presented in this study improve not only the current understanding of metal sequestration and surface precipitation at mineral/water interfaces but also shed light on the large differences in the surface reactivities of clay minerals with chain structure versus layered structure.